Knowledge and attitude towards antimicrobial self medication usage: a cross sectional study among medical and nursing students - Bala, Ritu; Singh, Harminder; Kaur, Kamlpreet; P, Girish; Kohli, Kamlesh (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Antimicrobial drug resistance is a fast mounting universal crisis. Many factors like self medication, inappropriate use and unregulated sale of medicines and self medication have been attributed to this problem. The objective was to determine extend and causes of antimicrobial self medication and to compare the knowledge attitude of senior and junior medical/nursing students. Methods: We conducted a cross-sectional study on randomly selected 410 students from Baba Farid University of Health Sciences Faridkot, Punjab. A total sample of 220 medical students were enrolled from GGS Medical College, Faridkot (1st year students 50 and 170 above 1st year senior medical students ) and 190 nursing students were enrolled from University College of Nursing, Faridkot. Results: prevalence of antimicrobial self medication came out to be around 74%. The most common cause for seeking antimicrobial (self therapy) was upper respiratory tract infection. A statistical significant knowledge/attitude gap was found between senior and fresher medical/nursing students. Conclusions: High prevalence of antimicrobial self medication among medical/nursing students is a matter of concern and it should be discouraged at appropriate level to safeguard students from preventable adversary exposure.